MODELLING AND SIMULATION OF ELECTRIC VEHICLE IMPACT ON NOISE MAP ALTERATIONS IN COMMERCIAL ZONES OF BANDUNG CITY (A CASE STUDY OF TUGU SIMPANG LIMA TO BANDUNG CITY SQUARE) - Tuzzahra Haswinanda, Athaya
The number of electric vehicles in Indonesia is expected to increase rapidly in the coming years, leading to a significant reduction in motor vehicle noise levels. This noise reduction not only improves environmental quality but also has important implications for noise mapping, an essential tool for identifying noise sources in urban environments. This study focuses on noise analysis in the commercial area of Bandung, specifically in the Tugu Simpang Lima to Alun-alun area, using noise mapping simulations based on various scenarios of electric vehicle (EV) penetration. The noise modeling uses the NMPB08 standard, allowing for inputting noise data from internal combustion engine (ICE) vehicles and EVs. The simulation results show a decrease in noise levels as the percentage of EVs increases. In the 100% ICE scenario, day-night noise levels (Lsm) range from 66.46 to 75.76 dBA. Meanwhile, in the 25%, 50%, 75%, and 100% EV scenarios, the average noise reduction is 1.21 dBA, 2.88 dBA, 5.64 dBA, and 17.8 dBA, respectively. This significant change in noise maps also indicates potential zoning changes. In the 25% and 50% EV scenarios, the area could be developed into commercial and service zones, while in the 75% and 100% EV scenarios, the area has the potential to be converted into residential and housing zones, as well as environments that support facilities such as hospitals, schools, and places of worship. The increase in natural air circulation through building openings also becomes possible, providing additional benefits in terms of energy efficiency and occupant comfort.